Understanding supply chain knowledge mobilization barriers from the middle‐range perspective: an empirical investigation of Argentina's agri‐food industry - Zhao, Guoqing; Xie, Ying; Dennehy, Denis; Fosso Wamba, Samuel (Wiley, 2025)
Despite considerable research attention to supply chain knowledge mobilization (KMob) barriers, understanding of why, how, and when they emerge in practice remains limited. We address this knowledge deficit by using middle‐range theory (MRT) as a theoretical lens to examine supply chain KMob barriers in their naturally occurring environment. Drawing on 42 in‐depth, semi‐structured interviews with Argentinian agri‐food supply chain (AFSC) practitioners, we present novel insights into the emergence of AFSC KMob barriers. First, our findings indicate the prevalence of 11 individual, intra‐organizational, and inter‐organizational KMob barriers in Argentinian AFSCs. Second, Argentina's political, economic, social, technological, legal, and cultural (PESTLC) environment contribute to these barriers. For example, the cultural environment, characterized by strong hierarchy and weak intellectual autonomy, may have negative effects on AFSC practitioners' KMob behaviors and perceptions, resulting in resistance to knowledge sharing, while long‐term political and economic instability poses challenges for intra‐ and inter‐organizational KMob. Third, these 11 KMob barriers elicit both semantic and pragmatic knowledge boundaries that thwart AFSC KMob. Our study extends the applicability of MRT to supply chain KMob research and provides a framework for better understanding KMob barriers. The study has important implications for agricultural research institutions and focal companies of local AFSCs.
Keywords: agri-food supply chains; Argentina; middle-range theory; semi-structured interviews; supply chain knowledge mobilization; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 8.1 Organisation and delivery of services; Business & Management; 3507 Strategy, management and organisational behaviour; 3509 Transportation, logistics and supply chains